Desenvolvimento de interfaces web adaptado para portadores de daltonismo - Hruba, Filipe Franchini (2018)
With the great availability of Internet access, a portion of users may present some limitations that may hinder access to information, such as visual impairments. Thus, Web acessibility becomes increasingly relevant and fundamental so that everyone can access information in the same way. As the use of colors is very present in Web interfaces, users with color blindness may have difficulties in understanding and interacting with these interfaces efficiently. In view of these difficulties, this study aims to develop acessible web development heuristics for the colorblind based on regarded accessible Web development concepts and guidelines. Then, apply these heuristics in a tool to assist in the development of Web interfaces that adapt to each condition of color blindness. For the tool’s development, it was used the source code of the Web development framework Materialize. As the resulto f this work, an open and adaptable tool was developed, which aims to assist in the development of Web interfaces capable of adapting itself in real time to different condition of color blindness.